2021
DOI: 10.1186/s41479-021-00087-6
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein D: a useful marker for differentiation of drug-induced pneumonia and bacterial pneumonia

Abstract: Background Drug-induced pneumonia (d-pneumonia) and bacterial pneumonia (b-pneumonia) are often difficult to differentiate; therefore, this study examined the possibility of differentiating them using serum biomarkers. Methods The study included 22 and 16 patients diagnosed with b- and d-pneumonia, respectively, at our institution or affiliated institutions. For d-pneumonia, the causative drug was minocycline hydrochloride in four patients, gefitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…KL-6 and SP-D levels were positive during treatment with abemaciclib prior to consultation with us and improved with treatment (figure 2). KL-6 is an MUC1 mucin protein and has been observed in adenocarcinoma of various cancer cell lines, including breast cancer,10 whereas SP-D is considered a useful marker of drug-induced pneumonitis 11. Since the severity of abemaciclib-induced pneumonitis ranges from mild to fatal, monitoring these multiple diagnostic arms and collaborative consultation with pulmonologists may be highly effective in preventing drug-induced pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…KL-6 and SP-D levels were positive during treatment with abemaciclib prior to consultation with us and improved with treatment (figure 2). KL-6 is an MUC1 mucin protein and has been observed in adenocarcinoma of various cancer cell lines, including breast cancer,10 whereas SP-D is considered a useful marker of drug-induced pneumonitis 11. Since the severity of abemaciclib-induced pneumonitis ranges from mild to fatal, monitoring these multiple diagnostic arms and collaborative consultation with pulmonologists may be highly effective in preventing drug-induced pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…KL-6 is produced by actively regenerating type II alveolar epithelial cells, whereas SP-D is produced by type II alveolar epithelial cells once they have matured and regenerated [ 29 ]. In addition, the activation of a specific enzyme is necessary to cleave KL-6 from the cell membrane, and it is thought that more severe injury must occur to increase circulating KL-6 levels [ 30 ]. These functional differences may explain the differences in serum concentrations.…”
Section: Serum Biomarkers Of Lung Epithelial Cellsmentioning
confidence: 99%
“…Some studies on serum biomarkers in DRP have reported that absolute levels at the onset or changes from the baseline of KL-6 can predict the clinical outcomes of DRP [ 14 , 37 ]. KL-6, SP-D, and SP-A can be different and not associated, depending on the situation in DRP [ 30 , 38 ]. There have been no reports that have focused on serum biomarkers in DRP-HP.…”
Section: Serum Biomarkers Of Drp-hpmentioning
confidence: 99%